THU0113 Rosuvastatin Improves Inflammation and Vascular Function in Rheumatoid Arthritis. (10th June 2014) - Syngle, A.; Garg, N.; Krishan, P.
Abstract : Background: Increased cardiovascular risk in patients with rheumatoid arthritis (RA) provides a strong rationale for early therapeutical interventions. In view of the similarities between atherosclerosis and RA 1 and the proven benefit of statins in atherosclerotic vascular disease, rosuvastatin is being investigated in RA. Objectives: To delineate the impact of rosuvastatin on endothelial function and adhesion molecules as well as on markers of inflammation in patients with RA. Methods: 76 RA patients were randomized to receive 6 months of treatment with rosuvastatin (10mg/day, n=38) or placebo (n=38) as an adjunct to existing stable antirheumatic drugs. Flow mediated dilatation (FMD) was assessed by Angiodefender™ (Everest Genomic Ann Arbor, United States). Inflammatory measures included Disease activity score of 28 joints (DAS28), CRP and ESR were measured at baseline and after treatment. Estimation of serum nitrite, Lipids, Pro-inflammatory cytokines (TNF-α, IL-6 and IL-1) and adhesion molecules (ICAM-1 and VCAM-1) was done at baseline and after treatment. Results: At baseline, inflammatory measures, pro-inflammatory cytokines and adhesion molecules were elevated among both groups. At baseline, significant correlation was found between FMD and CRP and ICAM-1 in the rosuvastatin group while significant correlation was found between FMD and CRP in the placebo group. FMD increased significantly (p<0.01) after treatment with rosuvastatin but did not show significant change with placebo. After treatment, rosuvastatin exerted positive effect on lipid spectrum: lowering concentration of total cholesterol, LDL, elevation of HDL as compared with placebo. At 6 months, DAS28, ESR, CRP, TNF-α and IL-6 improved significantly on rosuvastatin as compared with placebo (Fig.1). Furthermore, concentrations of serum nitrite and ICAM-1 significantly lower in the rosuvastatin group compared with the placebo group. There was no significant improvement in IL-1 and VCAM-1 in both groups. Significant negative correlation observed between FMD and IL-6, ICAM-1, CRP and LDL after treatment with rosuvastatin. Conclusions: First study to show that rosuvastatin improves inflammatory disease activity and endothelial dysfunction in RA. Rosuvastatin lowers the proinflammatory cytokines, especially IL-6 and TNF-α, which downregulates adhesion molecules and CRP production and thus the production of NO. Reduction of cytokines and CRP favorably impacts the inflammatory disease activity. Rosuvastatin also favorably improved the lipid levels through HMG-CoA reductase inhibition and possibly through cytokine reduction. These factors in turn improve the endothelial dysfunction. The anti-inflammatory and vasculoprotective effects of rosuvastatin in RA appear to be due to its anti-proinflammatory cytokine effect and HMG-CoA reduction. Rosuvastatin can mediate modest but clinically apparent anti-inflammatory effects with modification of vascular risk factors in the context of high-grade autoimmune inflammation of RA.These finding suggests that vascular effects of rosuvastatin may provide a novel strategy to prevent cardiovascular events in these patients. References: Kaplan, M.J. Curr. Opin. Rheumatol. 2006;18:289-297 Acknowledgements: This study was supported by APLAR Research Grant. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.5290